The analysis of pressure distribution at a foot during breaststroke kicking motion - Tsunokawa, T.; Takeda, T.; Tsubakimoto, S. (Japanese Journal of Sciences in Swimming and Water Exercise, 2010)
The purpose of this study was to develop a method to predict fluid forces acting on the foot and to clarify those characteristics during breaststroke kicking motion. Three male competitive swimmers whose specialties were breaststroke participated in this study. They performed breaststroke kicking motion without upper limb motion at three different effort trials (Slow, Normal, Fast). The trials were recorded by digital video cameras (60Hz) and we calculated coordinates of a right foot by using 3D-DLT method. Eight pressure sensors (200Hz) were attached on the right foot of swimmers and measured pressure distribution. Fluid forces acting on the foot were obtained by the way of multiplying measured pressure value and area of foot. As a result, fluid forces acting on the foot reflected the motion of foot. Furthermore, we found differences of influence by the change of effort each of subjects.